Sentralisasi Akuntansi Kantor Cabang oleh Kantor Pusat Pada PT Detofa Trinaka Nusantara Berdasarkan PSAK 1 - Sabrina Faylesia; Nanda Shafa Salsabila; Cindy Fasabillah Putri; Dina Khairida; Siti Rodiah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the practice of centralized accounting conducted by a company's head office for branch units that do not independently prepare financial statements. Within the framework of PSAK 1 on the Presentation of Financial Statements, a reporting entity is required to present its financial statements as a single economic entity. Employing a qualitative-descriptive approach and a literature review, this article demonstrates that the centralization of transaction recording from branch offices by the head office is a legitimate practice and aligns with the principles of PSAK 1, provided that all transactions are recorded in a reliable, accurate, and consistent manner. The study further identifies key advantages of centralized accounting systems, including improved efficiency and enhanced internal control, while also recognizing potential risks associated with reliance on information systems and inter-unit communication.